Overview of trends in the development of modern electronic document management systems - E. L. Gulkova; T. Е. Krikunova (Вестник университета)
This paper provides a brief analytical overview of strategic objectives of the digitalisation process within the framework of interaction between tax authorities and tax payers, including aspects of electronic document management (hereinafter referred to as EDM). The purposes of the article are to study organisational barriers within the framework of harmonisation of tax management systems and document processing systems as well as to assess the advantages and possible obstacles to the introduction of the EMD, which allows us to form an objective idea of the current state and prospects for the development of this area. The authors have analysed the practice of using electronic communication mechanisms and information exchange between participants in tax relations. The main problems arising during the monitoring and coordination of economic activity in the context of the use of modern automated digital solutions are highlighted, and potential prospects to overcome them are identified. The recommendations presented are intended to implement measures to address the projected risks associated with the process of integrating the EDM into existing tax procedures. The results obtained can be used in the development of solutions for the formation of an EDM system for organisations, in their interaction with tax authorities, and in the development of draft laws to improve the provisions of tax administration in the Russian Federation.